2020
DOI: 10.3390/md18100520
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Alginate as a Potential Therapeutic Filler: An In Vivo Study in Rats

Abstract: Filler injection demand is increasing worldwide, but no ideal filler with safety and longevity currently exists. Sodium alginate (SA) is the sodium salt of alginic acid, which is a polymeric polysaccharide obtained by linear polymerization of two types of uronic acid, d-mannuronic acid (M) and l-guluronic acid (G). This study aimed to evaluate the therapeutic value of SA. Nine SA types with different M/G ratios and viscosities were tested and compared with a commercially available sodium hyaluronate (SH) fille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…36 It is worth mentioning that the SM hydrogel we prepared was more likely to induce M1 polarization of macrophages. This phenomenon was similar to the previous research, 37,38 probably ascribing to the lack of purification of SA, given that it has been reported that the effect of SA on macrophage activity differs depending on the degree of purification, the M/G ratio, and viscosity. 39,40 Our study indicated that loading HM may be a powerful method for regulating the macrophage response in SM-based hydrogels.…”
Section: Smh Regulated Macrophages To Differentiate Into the M2 Pheno...supporting
confidence: 91%
“…36 It is worth mentioning that the SM hydrogel we prepared was more likely to induce M1 polarization of macrophages. This phenomenon was similar to the previous research, 37,38 probably ascribing to the lack of purification of SA, given that it has been reported that the effect of SA on macrophage activity differs depending on the degree of purification, the M/G ratio, and viscosity. 39,40 Our study indicated that loading HM may be a powerful method for regulating the macrophage response in SM-based hydrogels.…”
Section: Smh Regulated Macrophages To Differentiate Into the M2 Pheno...supporting
confidence: 91%
“…The insignificant inflammatory reaction caused by gene-activated SA-based scaffolds during their intramuscular implantation, in our opinion, is due to the moderate toxic effect of the incorporated transfecting complexes when they are released into the surrounding tissues, as well as an increase in the local divalent ion concentration leading to the attraction of leukocytes from blood vessels to the implantation zone [ 37 ]. However, these results, in general, correspond to the standard foreign body reaction to gradually degrading biomaterials [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sodium alginate (SA), an anion- and water-soluble linear polysaccharide, comprises 1-4-linked β-D-mannuronate (M) and α-L-guluronate (G) [ 32 ]. SA has been widely employed in pharmaceutical excipients for its fascinating advantages (including its safety, biocompatibility, and biodegradability [ 33 , 34 , 35 , 36 ]). SA is relatively low-cost and easily available via the isolation from cell walls of brown algae ( Ascophyllum nodosum and Laminaria digitate ) as compared with polymers and polyelectrolytes [ 33 , 37 ].…”
Section: Introductionmentioning
confidence: 99%